Case reports of robot-assisted laparoscopic radical nephrectomy and inferior vena cava tumor thrombectomy: A retrospective analysis. Issue 33 (20th August 2021) - Ma, Shuaijun; Jia, Weijing; Hou, Guangdong; Quan, Penghe; Zhang, Longlong; Fan, Xiaozheng; Yang, Bo; Su, Xing; Jiao, Jianhua; Wang, Fuli; Yuan, Jianlin; Qin, Weijun; et al.
Abstract : Abstract: Renal cell carcinoma is one common type of urologic cancers. It has tendencies to invade into the inferior vena cava (IVC) and usually requires an open surgery procedure. High rates of operative complications and mortality are usually associated with an open surgery procedure. The recently emerged robot-assisted laparoscopic radical nephrectomy (RAL-RN) and IVC tumor thrombectomy have shown to reduce operative related complications in patients with renal cell carcinoma. This case series study aimed to summarize technical utilization, perioperative outcomes, and efficacies of RAL-RN and IVC tumor thrombectomy in our hospital. A retrospective analysis was performed on clinical data from 20 patients who underwent RAL-RN and IVC tumor thrombectomy from January 2017 to December 2019 in our department. Patients had a median age of 59 years (interquartile range [IQR], 46–68). Four patients had renal neoplasm on left side and 16 on right side. Nineteen patients underwent RAL-RN (level 0: n = 2) or RAL-RN with IVC thrombectomy (n = 17) (level I: n = 3; level II: n = 12; and level III: n = 3) and 1 patient was converted into an open surgery. The median operative time was 328 minutes (IQR, 221–453). The estimated median blood loss was 500 mL (IQR, 200–1200). The median size of removed renal carcinoma was 67 cm 2 (IQR, 40–91); the length of IVC tumor thrombus was 5 cm (IQR, 3–7). The postsurgery hospital length of stay was 6 days (IQR, 5–7). The complications included intestinal obstruction (n = 1), lymphatic fistula (n = 1), heart failure (n = 1), and low hemoglobin level (n = 1). The outcomes for patients after 16 months (IQR, 11–21) follow-up were tumor-free (n = 10), tumor progression (n = 4), loss of contact (n = 1), and death (n = 5). We concluded that RAL-RN and IVC thrombectomy renders good safety profiles including minimal invasiveness, low estimated median blood loss, short hospitalization, low morbidity, and quick renal function recovery. The long-term efficacy needs a further investigation.